Acoustic correlates of word stress production in the connected speech of american english and brazilian portuguese speakers - Ribeiro, Thais Sada (2006)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.